ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN TAHUN 2021-2023 PADA PT. INDUSTRI JAMU DAN FARMASI SIDO MUNCUL Tbk.: Kinerja keuangan PT. industri Farmasi Sido Muncul Tbk. - ., Gugun; Mega Septiyani, Putri; Nursyaidah, Zakiah; Dasman, H. Sunita (Ekonomi & Bisnis, 2024)
This research aims to analyze the financial statements of PT Industri Jamu dan Farmasi Sido Muncul Tbk. This study will provide a clearer picture of the issues arising at PT Industri Jamu dan Farmasi Sido Muncul Tbk. From this research, revenue, profit and loss, and liabilities become the main points that influence the progress of the company. In this study, the method used is a quantitative descriptive method with trend analysis. Furthermore, it was found that in the years 2021-2023, the data obtained showed that the company experienced a decline.Keywords: Financial performance, Revenue and Profit, Assets and Liabilities, Financial Statements